A Rare, Recurrent, De Novo 14q32.2q32.31 Microdeletion of 1.1 Mb in a 20-Year-Old Female Patient with a Maternal UPD(14)-Like Phenotype and Intellectual Disability - Almira Zada; Farmaditya E. P. Mundhofir; Rolph Pfundt; Nico Leijsten; Willy Nillesen; Sultana M. H. Faradz; Nicole de Leeuw (Case Reports in Genetics)
We present a 20-year-old female patient from Indonesia with intellectual disability (ID), proportionate short stature, motor delay, feeding problems, microcephaly, facial dysmorphism, and precocious puberty who was previously screened normal for conventional karyotyping, fragile X testing, and subtelomeric MLPA analysis. Subsequent genome wide array analysis was performed on DNA from blood and revealed a 1.1 Mb deletion in 14q32.2q32.31 (chr14:100,388,343-101,506,214; hg19). Subsequent carrier testing in the parents by array showed that the deletion had occurred de novo in the patient and that her paternal 14q32 allele was deleted. The deleted region encompasses the DLK1/GTL2 imprinted gene cluster which is consistent with the maternal UPD(14)-like phenotype of the patient. This rare, recurrent microdeletion was recently shown not to be mediated by low copy repeats, but by expanded TGG repeats, flanking the 14q32.2q32.21 deletion boundaries, a novel mechanism of recurrent genomic rearrangement. This is another example how the application of high resolution genome wide testing provides an accurate genetic diagnosis, thereby improving the care for patients and optimizing the counselling for family.